Ras-related protein Rab-20 inhibition alleviates cerebral ischemia/reperfusion injury by inhibiting mitochondrial fission and dysfunction - Guo, Jia; Zhang, Lu; Bu, Yujie; Li, Wenjuan; Hu, Jianping; Li, Jianxiong (Frontiers in Molecular Neuroscience, 2022)
Ras-related protein Rab-20 (Rab20) is induced in hypoxia and contributes to hypoxia-induced apoptosis. However, the role and mechanism of Rab20 in cerebral ischemia/reperfusion (I/R) injury need to be elucidated. We established a cerebral I/R injury model in the mice and an oxygen-glucose deprivation/reoxygenation (OGD/R) model in HT22 cells to determine the effects of Rab20 in cerebral I/R injury. Rab20 expression was upregulated in mice after I/R and in HT22 cells after OGD/R. Upregulated Rab20 was mainly located in neurons. Rab20 inhibition significantly alleviated brain infarct volume, neurological deficits, and neuronal apoptosis in mice after I/R. Moreover, Rab20 knockdown significantly ameliorated the OGD/R-induced inhibition of cell viability and apoptotic cell death in HT22 cells. Rab20 knockdown significantly alleviated OGD/R-induced mitochondrial fission by repressing mitochondrial dynamin-related protein 1 (Drp-1) recruitment and increasing Drp-1 (Ser637) phosphorylation and ameliorated mitochondrial dysfunction by reducing the mitochondrial reactive oxygen species (ROS) and cellular calcium accumulation and increasing the mitochondrial membrane potential. In addition, Rab20 knockdown significantly alleviated cytochrome c release from the mitochondria into the cytosol in HT22 cells after OGD/R. Rab20 contributes to cerebral I/R injury by regulating mitochondria-associated apoptosis pathways. Targeting Rab20 may be an attractive strategy for the treatment of cerebral I/R injury.